Identificação de biomarcadores para casos de microcefalia - Nóbrega, Renata Valéria (2020)
Microcephaly is a clinical finding and can result from congenital anomalies or originate after delivery. Congenital malformations, including microcephaly, have a complex and multifactorial etiology, which can occur as a result of infectious processes during pregnancy. The increase in microcephaly reports in Brazil triggered great difficulties in the specific diagnosis and identification of the etiological agents of microcephaly. Thus, it becomes evident the need to develop new diagnostic methodologies that facilitate and make the diagnosis of microcephaly cheaper. In this sense, the main objective of this study was to identify biomarkers for cases of microcephaly. To meet this objective, the study population consisted of children born and cared for in public health services in the state of Paraíba, as of August 1, 2015. The sample was composed of two groups, one being experimental, formed by children with microcephaly and a control, composed of cognitively healthy children cared for in the health services of the Paraíba State Network. The research involved the following steps: 1- identification of biomarkers from an integrative review; 2- validation of biomarkers in blood samples; and 3- development of the diagnostic kit. The data were presented in the format of mean ± standard error of the mean. Statistical analyzes of the results were performed by comparing the means, to determine the differences between the groups, as well as by correlation tests, to determine the interrelationship of the biomarkers and microcephaly. The research project was approved by the Research Ethics Committee (CEP), opinion number 2,242,701, following the rules of the National Research Ethics Commission (CONEP) for research involving human beings (Resolution No. 466/12 of the National Council de Saúde / MS.dispensável At the end of the integrative review, 2 genes with the greatest potential to serve as markers for microcephaly were identified, namely: alpha-synuclein (SNCA) and neuregulin (NRG). some pairs of primers for each gene and after evaluation, the most efficient pairs were identified for each gene. Subsequently, PCR analyzes were performed and it was verified for both genes an increase in expression in the microcephalic group, demonstrating that these genes can be used as markers for microcephaly. Finally, we point out that the identified markers are essential to produce a diagnostic kit for microcephaly provides a f essential tool to solve the great laboratory difficulty of specific diagnosis of the cases of this syndrome. In addition, the development of this kit resulted in obtaining a biotechnological resource aimed at advances in public health.